A Designing Dairy Cattle Facilities Based on Statics and Dynamic Zoometry by Using Artificial Neural Network - Sugiono Sugiono; Rudy Soenoko; Rio L Lukodono (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2017)
The dairy cattle productivity is very depending on the quality of their facilities and their environment condition. A lot of researches have been done in this area, but it is not developing the knowledge of animal dimensions and behaviours correlated with their facilities design. Complexities of dynamics zoometry is very depending on cow behaviours that it forced to use neural network (NN) approaching. Hence, the purposes of the paper  is to create the concept of static and dynamic zoometry approach to guide the ergonomics facilities design and the modern of dairy cattle house based on zoometry data by using artificial neural network. The research is started with study literature of anthropometry, CAD design, dairy cattle, facility design and neural network. The next step is collecting the data of cow dimensions for static zoometry (17 variables) and cow behaviours for developing the concept of dynamics zoometry (5 variables). The static data is used as input factor and dynamic data as desire of Back Propagation NN model. The result of BPNN training is used to design the dairy cattle facilities, e.g. 3D CAD house with minimal length = 357.67 cm, minimal width = 132.03 cm (per tail) and minimal height = 205.28 cm. Finally, the paper is successfully developed the concept of zoometry approach and BPNN model as pioneer of implementing comfort knowledge.